Statistical Analysis of Association, Heterosis, and Inheritance of Grain Yield Contributing Quantitative Traits in Segregating Lines of Wheat (Triticum aestivum L.) - Panhwar, N. A.; Ahmed, S. R.; Lahori, A. H.; Mierzwa-Hersztek, M.; Afzal, A.; Vambol, V.; Memon, A. H.; Panhwar, S. A.; Tunio, M.; Buriro, S. A.; Vambol, S. (Journal of Environmental Accounting and Management, 2026)
Wheat (Triticum aestivum L.) is great yielder with wide adaptability of stable food for huge population. In this study, twelve wheat F_4 segregating lines of bread wheat (Triticum aestivum L.) viz. Blue silver x M-154, Blue silver x Z.A-77, Blue silver x Pavon, M-154 x Blue silver, M-154 x Z.A-77, M-154 x Pavon, Z.A-77 x Blue silver, Z.A-77 x M-154, Z.A-77 x Pavon, Pavon x Blue silver, Pavon x M-154 and Pavon x Z.A-77 including their parent cultivars viz. Blue silver, M-154, Z.A-77, and Pavon were evaluated for high grain yield, Heterosis, correlation of traits and heritability. The results of this research showed highly significant differences (>0.01%) among genotypes for main spike length, spikelet main spike^-1, grains main spike^-1, 100-grain weight plant^-1, and grain yield plant^-1 except plant height and fertile tillers plant^1. The transgressed segregation was noted in wheat F_4 lines for morphological traits. High heritability was noted in plant height (55.17), tillers plant^1 (51.0), main spike length (61.93), spikelet main spike^-1 (60.18), grains main spike^-1 (53.5), seed index plant^-1 (71.0) and grain yield plant^-1 (57.2). High heritability percentage for plant height (0.552%) and 100 seed weight (0.71%) was noted in wheat F_4 line Blue silver x Pavon. High heritability was noted in number of tillers plant^-1 of main spike length (61.93%) and spikelet main spike^-1 (60.18%) in Blue silver x Z.A-77. High heritability for grains, main spike^-1 (53.5%) was confirmed in wheat F_4 line Blue silver x M-154, for grain yield plant^-1 (57.2%) in wheat F_4 line M-154 x Z.A-77. These results indicated that wheat F_4 line Blue silver x Pavan, Blue silver x M154 and M154 x Z.A-77 offered favourable genetic material which could be included in the selection scheme for breeding high yield wheat under ex-situ conditions. Further studies are suggested for future breeding for wheat varietal development plan.